2012
DOI: 10.1111/j.1365-3059.2012.02594.x
|View full text |Cite
|
Sign up to set email alerts
|

A new risk indicator for botrytis leaf blight of onion caused by Botrytis squamosa based on infection efficiency of airborne inoculum

Abstract: Botrytis leaf blight (BLB) caused by Botrytis squamosa is a major leaf disease of onion. Various forecasting systems have been developed to help growers manage the disease. To improve forecasting reliability, the influence of temperature and wetness duration on B. squamosa infection was quantified by inoculating onion leaves with a conidial suspension and incubating them under various combinations of temperature (10-30°C) and leaf wetness duration (0-84 h). Infection was measured as the number of lesions per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…However, the LAMP assay does not require expensive technology or formal training for DNA extraction and the detection of inoculum (Notomi et al ., ), making it suitable for commercial use with grapevine growers conducting the detection analyses. This study, in conjunction with other studies (Falacy et al ., ; Carisse et al ., , ; Van der Heyden et al ., ), also demonstrates that there may be benefit to managing polycyclic diseases, at least those caused by other Erysiphales, using airborne inoculum detection assays. In both sampling years, the L‐LAMP detection results were not significantly different from that of the qPCR detection results, indicating that the extraction assay was sufficient for detection (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the LAMP assay does not require expensive technology or formal training for DNA extraction and the detection of inoculum (Notomi et al ., ), making it suitable for commercial use with grapevine growers conducting the detection analyses. This study, in conjunction with other studies (Falacy et al ., ; Carisse et al ., , ; Van der Heyden et al ., ), also demonstrates that there may be benefit to managing polycyclic diseases, at least those caused by other Erysiphales, using airborne inoculum detection assays. In both sampling years, the L‐LAMP detection results were not significantly different from that of the qPCR detection results, indicating that the extraction assay was sufficient for detection (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Only in a relatively few cases, have thresholds been identified that indicate a particular disease risk, e.g. 50 conidia m −3 d −1 of Erysiphe necator was identified in Quebec, but this was for a specific grape variety (cv Chancellor) (Carisse et al , 2009b ) and often the spore concentration or area under a spore curve needs to be combined with an infection model to indicate actual disease risk (Carisse et al , 2012 ).…”
Section: Sampler Locations: Field Rooftop and Mobile Platformsmentioning
confidence: 99%
“…Plant disease surveillance can be defined as the ongoing collection and analysis of data for making decisions regarding disease prediction and management. Detection and quantification of airborne inoculum contribute to fungal disease management by guiding decisions regarding control measures (Carisse et al ., ; Van der Heyden et al ., ). With recent advances in fungal molecular quantification techniques (Carisse et al ., ), aerobiological data are expected to play a critical role in plant disease surveillance.…”
Section: Introductionmentioning
confidence: 97%
“…Since then, several researchers have studied the correlation or association between disease or yield losses and airborne inoculum occurring on the same day or some days earlier (Carisse et al ., , ). Airborne spore monitoring in disease control management programmes has proven to be of practical use for pathogens such as Phytophthora infestans and Botrytis squamosa , the causal agents of tomato late blight and onion leaf blight respectively (Bugiani et al ., ; Carisse et al ., ; Van der Heyden et al ., ).…”
Section: Introductionmentioning
confidence: 97%